Diffusion of an enzyme: the role of fluctuation-induced hydrodynamic coupling - Illien, P; Adeleke-Larodo, T; Golestanian, R (EPL Association, 2017)
The effect of conformational fluctuations of modular macromolecules, such as enzymes, on their diffusion properties is addressed using a simple generic model of an asymmetric dumbbell made of two hydrodynamically coupled subunits. It is shown that equilibrium fluctuations can lead to an interplay between the internal and the external degrees of freedom and give rise to negative contributions to the overall diffusion coefficient. Considering that this model enzyme explores a mechanochemical cycle, we show how substrate binding and unbinding affects its internal fluctuations, and how this can result in an enhancement of the overall diffusion coefficient of the molecule. These theoretical predictions are successfully confronted with recent measurements of enzyme diffusion in dilute conditions using fluorescence correlation spectroscopy.